NILAI-NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN SYAIR BUNGE JAMBU KARYA SYAZSYA KAYUNG - Nadela, Liony Vidya; Priyadi, Antonius Totok; Seli, Sesilia (Universitas Tanjungpura, 2025)
This research aims to analyze and interpret the character education values in the poetry collection